IMPLEMENTATION OF THE SOROGAN METHOD IN NAHWU LEARNING USING THE YELLOW BOOK AT MADRASAH ALIYAH AL-HIKAM JOMBANG - Cholilah, Zahirotu; Syuhadak , Syuhadak; Agil , Idrus Muchsin Bin (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This qualitative descriptive study aims to describe the steps, advantages, and obstacles in implementing the sorogan method in learning nahwu using the yellow book in class XB of Madrasah Aliyah Al-Hikam Jombang. Data were collected through interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldana models which include data condensation, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the sorogan method involves three stages: preparation (preparation of lesson plans by teachers), implementation (learning with the sorogan method), and evaluation (teachers ask about the material and rules that have been taught). The advantages of this method include establishing closeness between teachers and students, teachers can monitor the development of student understanding directly, more personal guidance and direction, and increasing student independence and enthusiasm for learning. However, the main obstacle is time efficiency, where the individual sorogan process takes a long time, causing students waiting for their turn to feel bored and the class becomes less conducive. To overcome this, teachers give additional assignments to students waiting for their turn to keep the classroom atmosphere conducive. The sorogan method, with modifications, remains relevant for in-depth nahwu learning. ABSTRAKPenelitian deskriptif kualitatif ini bertujuan untuk mendeskripsikan langkah-langkah, kelebihan, dan kendala penerapan metode sorogan dalam pembelajaran nahwu menggunakan kitab kuning di kelas XB Madrasah Aliyah Al-Hikam Jombang. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model Miles, Huberman, dan Saldana yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan metode sorogan melibatkan tiga tahap: persiapan (penyusunan RPP oleh guru), pelaksanaan (pembelajaran dengan metode sorogan), dan evaluasi (guru menanyakan materi dan kaidah yang telah diajarkan). Kelebihan metode ini meliputi terjalinnya kedekatan antara guru dan siswa, guru dapat memantau perkembangan pemahaman siswa secara langsung, bimbingan dan arahan yang lebih personal, serta peningkatan kemandirian dan semangat belajar siswa. Namun, kendala utama adalah efisiensi waktu, di mana proses sorogan yang individual memakan waktu lama, menyebabkan siswa yang menunggu giliran merasa bosan dan kelas menjadi kurang kondusif. Untuk mengatasi hal ini, guru memberikan tugas tambahan kepada siswa yang menunggu giliran untuk menjaga suasana kelas tetap kondusif. Metode sorogan, dengan modifikasi, tetap relevan untuk pembelajaran nahwu yang mendalam.